The prognostic value of circulating tumor DNA in malignant melanoma patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Liu, Lei; Hou, Shufu; Zhu, Aiping; Yan, Bing; Li, Linchuan; Song, Dandan (Frontiers in Immunology, 2025)
BackgroundCirculating tumor DNA (ctDNA) is an emerging biomarker in malignant melanoma(MM), and high levels of ctDNA may reflect a higher tumor load. However, its prognostic value for MM receiving immune checkpoint inhibitors(ICI) remains controversial. This meta-analysis aimed to elucidate the prognostic significance of ctDNA in this patient population.MethodsWe conducted a comprehensive search of the PubMed, Cochrane Library, CNKI, and EMBASE databases, including studies published up to August 15, 2024, to investigate the prognostic impact of ctDNA in MM patients treated with ICI. Using a fixed-effects model, we systematically evaluated the association between ctDNA levels and key survival outcomes, including overall survival (OS) and progression-free survival (PFS). Additionally, funnel plots, Begg’s test, and Egger’s test were employed to assess potential publication bias.ResultsTwelve studies from eleven articles, involving a total of 1063 eligible MM patients receiving ICI therapy, were included. The results indicated that patients with detectable ctDNA before initiating ICI therapy had significantly poorer OS (HR = 3.19, 95% CI = 2.22–4.58, P < 0.001) and PFS (HR = 2.08, 95% CI = 1.61–2.69, P < 0.001). Furthermore, the detectability of ctDNA during treatment was also significantly associated with worse OS (HR = 4.57, 95% CI = 3.03–6.91, P < 0.001) and PFS (HR = 3.79, 95% CI = 2.13–6.75, P < 0.001).ConclusionsThis meta-analysis indicates that in MM patients receiving ICI therapy, detectable and high levels of ctDNA are significantly associated with poorer OS and PFS. Therefore, ctDNA can serve as a diagnostic and stratification tool prior to treatment, as well as an effective indicator for monitoring treatment response and disease progression.Systematic Review Registrationwww.inplasy.com, identifier INPLASY2024110018.